Prevalence of medications nonadherence and its associated factors among type 2 Diabetes Mellitus patient in primary health clinic in Kuantan - Md Aris, Mohd Aznan; Abdullah, Fa’iza; Wan Mansur, Wan Najwa Aima (2022)
Diabetes is a common non communicable disease in Malaysia. 1 • At this covid endemic era, patient’s perception on medication therapy may differ from the past. • There is no available data on adherence in Kuantan at this point of time. • This study is to recognise the characteristics of nonadherence patient, in order to give an early intervention and prevention.